FeS2 Grown Pencil Graphite as an In‐expensive and Non‐enzymatic Sensor for Sensitive Detection of Uric Acid in Non‐invasive Samples. Issue 12 (1st August 2019) - Sha, Rinky; Vishnu, Nandimalla; Badhulika, Sushmee
Abstract: While most electrochemical uric acid (UA) sensors are developed on the conventional electrodes and involve either multiple steps based synthesis routes and/or complicated fabrication processes, this paper is the first demonstration of direct growth of pyrite FeS2 on pencil‐graphite electrode (PGE) for non‐enzymatic UA sensing. FESEM images of the pyrite FeS2 ‐PGE reveal mesoporous microspherical structure of pyrite FeS2 along with graphite flakes of PGE and EDX, Raman spectroscopic data validate growing of pyrite FeS2 on PGE. The pyrite FeS2 ‐PGE sensor exhibited detection limit of 6.7 μM, excellent linearity, reproducibility, selectivity over glucose, urea, ascorbic acid with the sensitivity of 370 μA mM −1  cm −2 in the range of 10–725 μM of UA. These improved analytical performances can be attributed to high conductivity of the pyrite FeS2, larger electro‐active surface area of the mesoporous microspherical pyrite FeS2 grown on PGE (than only PGE) and abundance in defect sites originating from both the pyrite FeS2 as well as functional groups of pencil graphite. Furthermore, the sensor was validated against UA in urine sample and the result supports well with the UA concentration achieved from colorimetric technique. Development of this low cost, non‐enzymatic, sensitive and highly selective pyrite FeS2 ‐PGE bases UA sensor is a significant step in the development of practically viable sensors for point‐of‐care applications in clinical and pharmaceutical analyses. Abstract :